Innovation of Storytelling and Role-Playing Methods in Islamic Religious Education Learning - Rofiq, Ainur; Nisa, Khoirun; Muid, Abdul (At-tadzkir: Islamic Education Journal, 2024)
This article aims to analyze the roleplaying and storytelling methods in applying Islamic Religious Education in schools and Madrasahs. The technique used in this research is literature with content analysis. This method uses several sources from Google, Books, Dimension, and Scopus that are relevant to the theme. The findings of this article are as follows: The roleplaying model in the learning process aims for students to appreciate the role being played, put themselves in the situation of others that the teacher wants, and arrange the stages of the role. Motivation is the drive contained in a person to make changes to achieve specific goals. Roleplaying can stop when learners have had enough time to express their feelings about the role played and the other participants, discuss and evaluate, share experiences, and conclude. It takes a long time because roleplaying is carried out, and learning materials that will be used need to be prepared. Teachers must provide detailed explanations to students, have more speaking skills, take issues considered essential and can be an attractive force for students, provide examples for the first steps in the roleplaying model, and understand the events that will be carried out.